2005
DOI: 10.5006/1.3278162
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Microbiologically Induced Corrosion by Sulfate-Reducing Bacteria on Carbon Steel Using Hydrogen Permeation

Abstract: The mechanism of microbiologically infl uenced corrosion (MIC) on carbon steel (CS) by the bacteria Desulfovibrio desulfuricans subs. desulfuricans was studied using hydrogen permeation, open-circuit potential, and cathodic polarization techniques, in a concentrated culture medium containing bacteria cells (10 7 cell/mL) and ferrous ions (300 mg/L) designed to simulate a condition common in systems for the secondary recovery of crude oil, characterized by highly contaminated microenvironments that severely cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Romero in 2005 [114] worked out the mechanism of sulfate reducing bacteria in MIC of iron. According to his theory the first is the bacterial adsorption and iron sulfide production and then a micro-galvanic cell formation through the metallic surface and the iron sulfide.…”
Section: Mechanisms Of the Biocorrosionmentioning
confidence: 99%
“…Romero in 2005 [114] worked out the mechanism of sulfate reducing bacteria in MIC of iron. According to his theory the first is the bacterial adsorption and iron sulfide production and then a micro-galvanic cell formation through the metallic surface and the iron sulfide.…”
Section: Mechanisms Of the Biocorrosionmentioning
confidence: 99%
“…Stress corrosion cracking and hydrogen embrittlement are two types of damage often reported (De Romero et al, 2005;Koh et al, 2004). Localized corrosion pits on the metal surfaces can be induced by SRB via the CMIC and/or EMIC mechanisms.…”
Section: Corrosion Caused By Srbmentioning
confidence: 99%
“…135 Microbiological degradation of stone was found to be enhanced by the rapid growth of algae, cyanobacteria, and fungi which bore into it by releasing extracellular enzymes and metabolites. 136 Romero et al studied MIC by SRB on carbon steel by using hydrogen permeation, 137 and they observed that the sulfate reducing bacteria Desulfovibrio sulfuricans induces carbon steel corrosion due to the biogenic hydrogen sulfide released as the result of its metabolic processes.…”
Section: Microorganisms and Chemicalmentioning
confidence: 99%